2023
DOI: 10.3847/2041-8213/ace361
|View full text |Cite
|
Sign up to set email alerts
|

SBI++: Flexible, Ultra-fast Likelihood-free Inference Customized for Astronomical Applications

Abstract: Flagship near-future surveys targeting 108–109 galaxies across cosmic time will soon reveal the processes of galaxy assembly in unprecedented resolution. This creates an immediate computational challenge on effective analyses of the full data set. With simulation-based inference (SBI), it is possible to attain complex posterior distributions with the accuracy of traditional methods but with a >104 increase in speed. However, it comes with a major limitation. Standard SBI requires the simulated data to have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Thus, the difference between the emulator and FSPS results are in general well described by the reported uncertainties in the catalog. An additional valuable, independent check on the fidelity of the inferred parameters can likely be obtained via an alternative inference technique, since the latter is affected by different systematics (Wang et al 2023d), or by comparing to additional spectra. This approach will be examined in the next generations of stellar populations catalogs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the difference between the emulator and FSPS results are in general well described by the reported uncertainties in the catalog. An additional valuable, independent check on the fidelity of the inferred parameters can likely be obtained via an alternative inference technique, since the latter is affected by different systematics (Wang et al 2023d), or by comparing to additional spectra. This approach will be examined in the next generations of stellar populations catalogs.…”
Section: Discussionmentioning
confidence: 99%
“…The sampling method used is nested sampling (Skilling 2004), which is better suited to sample multimodal posteriors than other traditional techniques such as Markov Chain Monte Carlo (Goodman & Weare 2010). However, it has also been shown that nested sampling does not always accurately sample the global minimum when fitting for galaxy redshifts (Wang et al 2023d). Our finding is consistent with…”
Section: Appendix a Accuracy Of Parameters Inferred With The Neural N...mentioning
confidence: 99%
“…In practice, observational noise due to instrumental effects and measurement uncertainties might necessitate larger samples. While a detailed modeling of the noise considering wavelength coverage, resolution, extent of correlated noise across wave bands, and overall S/N is outside the scope of this work, including an accurate noise model in the forward modeling "simulator" in the SBI while training can significantly improve its robustness, especially with newer methods (e.g., SBI++; Wang et al 2023) being developed.…”
Section: How Do We Choose a "Population Of Galaxies" To Studymentioning
confidence: 99%
“…Using traditional SED fitting methods, analyzing 10 5 galaxies will take up to 2 × 10 6 CPU hr. Even with the development of accelerated SED fitting (e.g., Alsing et al 2020;Hearin et al 2023;Khullar et al 2022;Wang et al 2023), an analysis of 10 5 galaxies will still take up to ∼10 3 GPU hr. POPSED is able to recover the posterior of the population distribution for ∼10 5 galaxies within ∼10 GPU hr, 100 times faster than the SBIbased methods.…”
Section: Advantage Of Population-level Inference Using Popsedmentioning
confidence: 99%
“…This problem has been partially mitigated by recent developments in accelerating SED modeling by emulating the SPS models with neural networks (Alsing et al 2020), building differentiable SPS models with a high-performance library (Hearin et al 2023), and speeding up the sampling by using amortized simulation-based inference (SBI; Khullar et al 2022;Wang et al 2023). However, some of these methods need sophisticated training and are costly to retrain when adapting to different SPS models or noise properties.…”
Section: Introductionmentioning
confidence: 99%